EEG Findings in Infants With Neonatal Abstinence Syndrome Presenting With Clinical Seizures - Palla, Murali Reddy; Khan, Gulam; Haghighat, Zahra M.; Bada, Henrietta (Frontiers in Pediatrics, 2019)
Abstract: Neonatal abstinence syndrome (NAS) refers to a constellation of signs occurring in newborn infants who were exposed to opioids or opiates in utero. These manifestations include poor feeding, gastrointestinal disorders, abnormal sleep patterns, and neurological signs such as jitteriness, tremors, and seizures.1, 2 Myoclonus, jitteriness, and tremors often may be interpreted as seizures and therefore treated as epileptic seizures. Objective: To determine whether clinical seizures in infants with NAS correlate with electroencephalogram (EEG) findings. Design/ Method: We reviewed the standard EEG or video electroencephalogram (VEEG) of infants with NAS who were admitted because of seizures. Exclusion criteria included infants with abnormal chemistries or with clinical diagnosis other than NAS. Results: Forty neonates met study criteria; 28 had standard EEG recordings and 18 had VEEG. Mean gestational age was 38.5 weeks. The onset of seizures was as early as day 1 and as late as day 16 of life. Clinical seizures noted were jerking, rhythmic movement of the extremities, or tremors. Only three (7.5%) neonates had epileptic seizures. There were increased sharp transients in frontal, central, temporal, and or occipital regions. VEEG showed disturbed non-rapid eye movement (REM) sleep with frequent arousal, jittery movements, or sleep myoclonus. Conclusion: Clinical seizures correlate poorly with epileptic seizures in infants with NAS. A VEEG would be useful to confirm the presence of epileptic seizures prior to initiation of anti-seizure medications.